Pengaruh E-lifestyle dan E-hedonisme Terhadap Intens to Buy pada Generasi Milenial - Sari, Risca Kurnia; Utama, Satria Putra; Mondiana, Yani Quarta; Suprayitno, Didik (Jurnal Ilmiah Manajemen Kesatuan, 2022)
The purpose of this study was to analyze the effect of e-lifestyle and e-hedonism on the intensity to buy of the millennial generation. This type of research is a survey research. This research was conducted in Malang, East Java, with 150 respondents. The data analysis tool used in this research is SEM (Structural Equation Modeling), with Smart PLS as software. The results show that e-lifestyle has an effect on e-hedonism, e-lifestyle has no effect on intense to buy, e-hedonism has an effect on intense to buy, e-life style has an indirect effect on intense to buy through e-hedonism.